FUNGSI SOSIALISASI KELUARGA TERHADAP ANAK YANG MENGALAMI KETERLAMBATAN BICARA (SPEECH DELAY) DI KELURAHAN SUNGAI PAGAR KECAMATAN KAMPAR KIRI HILIR - Sumarni "; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT This research was conducted in Sungai Pagar Village, Kampar Kiri Hilir District, Kampar Regency with the aim of knowing: language development of children with speech delays. This study used a descriptive qualitative research method by taking 4 children as subjects. This study used a snowball sampling technique or snowball samples through data collection techniques using observation techniques, interviews, and documentation. Based on the results of research in the field, it can be concluded that language development based on the number of vocabulary children has in this study is still very minimal at the age of two. In addition, the average subject's articulation is still unclear and they are only able to pronounce fragments of words. But for non-verbal language development they are all very well. It turns out that children who experience speech delays are dominated by boys. Children who experience speech delays spend more time playing at home than playing and socializing in the surrounding environment. Parents give children the freedom to watch television and play mobile phones from when they were small until now without any control from their parents. The socialization function that occurs in families with children who are late in speaking does not go well because on average, the parents of the children do not have a special time to interact with their children, only communicating when the children are doing their activities. The socialization pattern used by parents on average uses a democratic socialization pattern, where parents give special rules to children in speaking, but are accompanied by reasons for the advice given. Keywords: Socialization Function, Speech Delay, Children